2008
DOI: 10.1016/j.ccr.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Transient Potent BCR-ABL Inhibition Is Sufficient to Commit Chronic Myeloid Leukemia Cells Irreversibly to Apoptosis

Abstract: The BCR-ABL inhibitor dasatinib achieves clinical remissions in chronic myeloid leukemia (CML) patients using a dosing schedule that achieves potent but transient BCR-ABL inhibition. In vitro, transient potent BCR-ABL inhibition with either dasatinib or imatinib is cytotoxic to CML cell lines, as is transient potent EGFR inhibition with erlotinib in a lung cancer cell line. Cytotoxicity correlates with the magnitude as well as the duration of kinase inhibition. Moreover, cytotoxicity with transient potent targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
192
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(223 citation statements)
references
References 24 publications
28
192
3
Order By: Relevance
“…Indeed, inhibition of PI3K-mediated signaling also enhances apoptosis sensitivity in GBM cells in an NHEJ-independent manner, as we have previously shown for agents that do not primarily cause DNA damage, that is, death receptor ligands such as TRAIL and anti-CD95 agonistic antibody (Opel et al, 2008). Intriguingly, in line with recent observations regarding the pharmacokinetics of inhibitor-induced cancer cell death (Shah et al, 2008), we also found that a brief, but potent inhibition of PI3K administered concurrently with a DNA-damaging drug is sufficient to commit GBM cells to apoptosis and to suppress clonogenic growth.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, inhibition of PI3K-mediated signaling also enhances apoptosis sensitivity in GBM cells in an NHEJ-independent manner, as we have previously shown for agents that do not primarily cause DNA damage, that is, death receptor ligands such as TRAIL and anti-CD95 agonistic antibody (Opel et al, 2008). Intriguingly, in line with recent observations regarding the pharmacokinetics of inhibitor-induced cancer cell death (Shah et al, 2008), we also found that a brief, but potent inhibition of PI3K administered concurrently with a DNA-damaging drug is sufficient to commit GBM cells to apoptosis and to suppress clonogenic growth.…”
Section: Discussionsupporting
confidence: 86%
“…Bim, a proapoptotic Bcl-2 homology 3-only protein (36), is elevated after ablation of Bcr-Abl and epidermal growth factor receptor signaling (37)(38)(39). However, our data showed that the levels of Bim were unperturbed after HHT treatment (Figs.…”
Section: Hht Induces Apoptosis In D816v Kit-expressing Cells and Decrcontrasting
confidence: 53%
“…The CrkL protein has been observed with a total of 28 PTMs identified in MS experiments (see www.phosphosite.org), however only phosphorylated tyrosine 207 (pTyr207) has been validated (using a range of methods including western blot, site-directed mutatgenesis and flow cytometry 30,[49][50][51][52][53][54] ). Tyrosine 207 phosphorylation has been shown to be the principle phosphorylation event related to BCR-ABL activity 30 .…”
Section: Anticipated Resultsmentioning
confidence: 99%